Beyond the tracks: Understanding the work-life dynamics of Indian railway drivers - Ranjan, Rajesh; Prasad, T; Singh, Rashmi; Tripathi, Saumya (Edelweiss Applied Science and Technology, 2025)
This study explores the relationship between work-life balance and quality of life among Indian Railways’ drivers (loco pilots). It specifically examines the concept of time balance, referring to the equal distribution of time between work and family life. The findings suggest that drivers who allocate more time to family than to work report a higher quality of life compared to those who prioritize work over family. This article proposes a conceptual framework identifying the key factors influencing work-life balance among Indian Railways’ drivers, including organizational policies and their impact on personal well-being. Finally, this study discusses the broader implications of these findings and suggests directions for future research.